Political and Legal Responses to Human Mobility in South America in the Context of the Covid-19 Crisis. More Fuel for the Fire? - Acosta, Diego; Brumat, Leiza (Frontiers in Human Dynamics, 2020)
During the XXI century, South America has been the epicentre of vibrant discussions on human mobility. A new vocabulary emerged with legal principles such as the non-criminalization of irregular migration or the right to migrate as a fundamental right taking central stage. The combination of the arrival of COVID-19 together with the important emigration of Venezuelans in the region, as well as economic and political crisis are putting into question some of these advances and present a complex scenario of migration governance in the region for the years to come.